Communication Costs, Information Acquisition, and Voting Decisions in Proxy Contests - Bhattacharya, Utpal (Review of Financial Studies, 1997)
This article synthesizes some recent progress in the theories of corporate control and political lobbying to model the proxy campaign as a political campaign. The model yields a number of testable implications, only some of which have been examined in the literature. For example, if the loss from voting for a "bad" dissident exceeds the gain from voting for a "good" dissident, the model predicts that as communication costs fall, the number of proxy fights increases, announcement day returns decrease, and the fraction of dissident wins first increases and then decreases. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.